The Identification of the Range of Ixodidae Ticks and the Epidemiological Evaluation of Lyme Disease and Spotted Fever Rickettsiosis in Kansas from 2008 to 2012 - Coleman, Sara (My University, 2013)
This study evaluates the presence of both Lyme disease and Spotted Fever Rickettsiosis tick vectors throughout the state of Kansas, as well provides a descriptive epidemiology of Lyme disease and Spotted Fever Rickettsiosis cases in Kansas from 2008 to 2012. Data used to create maps providing tick vector locations was gathered from unpublished and published literature sources that had previously identified the tick vector. Data regarding the number of probable and confirmed cases, age, gender, race, ethnicity, seasonality, exposure, and clinical presentation was gathered from two surveillance systems used by the Kansas Department of Health and Environment. Results show that the tick vector, Ixodes scapularis, has been moving and expanding over time, and is now found in 23 Kansas counties. Additionally, we see that Dermacentor variabilis is present in 57 counties in Kansas, while Rhipicephalus sanguineus has only been identified in 4 counties in Kansas. The epidemiology study shows that there is an above average incidence of Spotted Fever Rickettsiosis in Kansas compared to the incidence in the United States, while Lyme disease continues to remain below the reported incidence for the United States. Results would indicate that tick-borne disease is present and increasing in Kansas due to tick vector expansion and increased exposure to tick habitats.
Keywords: Lyme Disease; Spotted Fever Rickettsiosis; Public Health; Public Health (0573)